1970
DOI: 10.1126/science.167.3924.1454
|View full text |Cite
|
Sign up to set email alerts
|

Underwater Vision

Abstract: 31. M. L. Hair (private communication) states that, at pressures of 16 torr and above, the very rapid increase in the amount of absorbed water makes it difficult to make precise measurements, and a fairly broad range of values for the number of molecules absorbed per hydrogen-bonded hydroxyl pair may be indicated. Hair's failure to produce anomalous water may have been due to the special nature of the surface treatment, which may prevent a clustering of hydroxyl pairs sufficient to form successive layers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0
1

Year Published

1977
1977
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 29 publications
1
34
0
1
Order By: Relevance
“…Distance perception underwater is typically overestimated relative to the same distances above ground (Luria and Kinney 1970;Luria et al 1967;Ross 1967). Researchers attribute this overestimation to optical factors such as reduced brightness contrast or seemingly increased aerial perspective.…”
mentioning
confidence: 99%
“…Distance perception underwater is typically overestimated relative to the same distances above ground (Luria and Kinney 1970;Luria et al 1967;Ross 1967). Researchers attribute this overestimation to optical factors such as reduced brightness contrast or seemingly increased aerial perspective.…”
mentioning
confidence: 99%
“…However, P. rivalis sp. nov. is present in shallow waters where PAR is restricted to the red end of the spectrum (Luria & Kinney 1970). It would be useful to study the photosynthetic pigment characteristics of P. rivalis sp.…”
Section: Discussionmentioning
confidence: 99%
“…Later research has shown that such adjustment not only extends to displacements in spatial location, but also to distortions in target form and size (25,30). In addition, other studies have indicated that observers can adapt to an even broader range of perceptual and motor aberrations including distortions in size and distartce (22,24), apparent curvature (27), and illusory motion (8) that occur underwater and the disabilitating effects produced by time-delayed visual feedback on perceptual-motor performance in virtual environment. Of particular relevance to the G-LOC problem are studies demonstrating sensory-motor adaptation to aberrations that appear in the microgravity conditions of parabolic and orbital flight (19).…”
Section: G-loc Adaptationmentioning
confidence: 99%